Integrating a Gender Equality Lens : Drawing Lessons from Three Good-Practice Development Policy Operations - Elefante, Marina; Robakowski, Anja (World Bank, Washington, DC, 2020)
This note provides guidance on how to best identify and address gender gaps through one of the World Bank Group’s core financing instruments, Development Policy Financing (DPF).The note describes three examples of reforms carried out under DPF that were selected for their exemplary approach to addressing gender gaps by leveraging on governments’ motivation or potential wins. Based on the examples, the note draws general lessons that can be applied to other projects, encouraging replication of good practice. The purpose of this note is thus to serve as a guide on how to address gender gaps through DPF.